2023
DOI: 10.3389/fncel.2023.1183232
|View full text |Cite
|
Sign up to set email alerts
|

Increasing reproducibility in preclinical stroke research: the correlation of immunofluorescence intensity measurements and Western blot analyses strongly depends on antibody clonality and tissue pre-treatment in a mouse model of focal cerebral ischemia

Anna Prehn,
Constance Hobusch,
Wolfgang Härtig
et al.

Abstract: In the setting of stroke, ischemia not only impairs neuronal function, but also detrimentally affects the different components of the neurovascular unit, which are shown to be involved in the transition from reversible to long-lasting tissue damage. In this context, the glial proteins myelin basic protein (MBP) and the 2′,3′-cyclic-nucleotide 3′-phosphodiesterase (CNP) as well as the vasculature-associated basement membrane proteins laminin and collagen IV have been identified as ischemia-sensitive elements. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 81 publications
0
0
0
Order By: Relevance
“…Consequently, future studies should include techniques allowing the best possible detection of protein levels in specific brain areas, e.g., via Western blot analyses circumscribed to these areas. This seems important, as a recent study demonstrated that either increasing or decreasing the immunosignal does not necessarily correspond with changed protein levels in the same direction [45]. Moreover, future studies need to be focused on the functional relevance of ischemiarelated alterations in tricellulin, MFAP5 and α-catenin, for example in respective knock-out animals.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, future studies should include techniques allowing the best possible detection of protein levels in specific brain areas, e.g., via Western blot analyses circumscribed to these areas. This seems important, as a recent study demonstrated that either increasing or decreasing the immunosignal does not necessarily correspond with changed protein levels in the same direction [45]. Moreover, future studies need to be focused on the functional relevance of ischemiarelated alterations in tricellulin, MFAP5 and α-catenin, for example in respective knock-out animals.…”
Section: Discussionmentioning
confidence: 99%